IJCM_247A: Perception of Medical Students on Family Adoption Programme; A Study conducted in a Medical College of Odisha. - Patra Priya Ranjan; Panda Jasmin Nilima; Bisoyi Sasmit Kumari; MadhabSatapathy Durga (Wolters Kluwer Medknow Publications, 2024)
Background: Community engagement in medical education gives the students an insight into the living conditions of the public and how they influence their health. Community Medicine department accomplish this through field practice and family health studies. The Family Adoption Programme (FAP), newly mandated for all medical undergraduate students, brings its own set of challenges and opportunities. Family Adoption Programme aims to provide an experiential learning opportunity to Indian medical graduates towards community-based health care and thereby equity in health Objectives: 1. To study the perceptions of Phase I MBBS Students on Family Adoption Program. 2. To determine the output of FAP implementation in MBBS curriculum. Methodology: A Cross-sectional study was conducted between August to November 2023 including 1st year MBBS students of MKCG Medical College, Berhampur, Odisha. A brief orientation was conducted by Dept. of Community Medicine on needs and competencies of FAP as recommended by the National Medical Commission(NMC). Students were sensitized to the FAP proforma prepared by the department. Periodic FAP visits for students in 4 groups was planned & conducted along with their assigned mentors at the selected nearby village. During these visits, students interacted with the families and details regarding health profile of the family were documented. Students perception & feedback was taken by Questionnaire using Google Form. A total 250 students were enrolled in FAP and 172 submitted their feedback. Data was analyzed using appropriate statistical tests and software. Results: The study included 172 1st year MBBS students with age range of 18-26 years & mean age of 20.58± 1.315 years. Among them, 66.9% were males & 33.1% were females.66.9% of students responded that FAP was a very good experience.55.2% of study participants were satisfied with their adopted family. Most of the students were interested to be a part of such activity throughout the professional years. Conclusion: Implementation of FAP requires meticulous planning, intersectoral co-ordination, good sensitization and training activities